The Embryo MADS Domain Protein AGAMOUS-Like 15 Directly Regulates Expression of a Gene Encoding an Enzyme Involved in Gibberellin Metabolism - Wang, Huai (American Society of Plant Biologists, 2004)
AGL15 (for AGAMOUS-Like 15) is a member of the MADS domain family of DNA binding transcriptional regulators that accumulates to its highest amounts during embryo development. To better understand how AGL15 functions, a chromatin immunoprecipitation approach was used to identify directly regulated genes. One DNA fragment that coprecipitated with AGL15 corresponded to a portion of the regulatory region of a gene named DTA1 (for Downstream Target of AGL15-1). The expression of DTA1 was positively correlated with AGL15 abundance during embryogenesis. In this report, a cis element for response to AGL15 was identified, and the activity of DTA1 as a gibberellin (GA) 2-oxidase was confirmed. DTA1 corresponds to AtGA2ox6 and was renamed to indicate this identity. Further experiments related the function of AtGA2ox6 to regulation by AGL15. Constitutive expression of AGL15 and of AtGA2ox6 altered endogenous GA amounts and caused GA-deficient phenotypes in Arabidopsis thaliana that could be at least partially rescued by application of biologically active GA. The phenotype of plants with decreased expression of AtGA2ox6 was the converse of plants overexpressing AtGA2ox6 in terms of seed germination attributes and effects on somatic embryo production.